กลาสโกว์ โคมา สเกล - โพทะยะ, โสพรรณ (Journal of The Royal Thai Army Nurses, 2018)
กลาสโกว์ โคมา สเกล เป็นมาตรวัดระดับความรู้สึกตัวของผู้ป่วยบาดเจ็บสมองที่เป็นมาตรฐานสากล ซึ่งใช้กันอย่างแพร่หลายมากว่าสี่สิบปี และมีการปรับปรุงพัฒนามาตรวัดมาเป็นระยะ การเข้าถึงข้อมูลเกี่ยวกับมาตรวัดที่เป็นปัจจุบันจะช่วยให้ผู้ใช้สามารถใช้มาตรวัดได้อย่างมีประสิทธิภาพ บทความนี้เป็นการนำเสนอวิธีใช้มาตรฐานมาตรวัด หลักเกณฑ์ ขั้นตอนและวิธีการใช้มาตรวัดในการประเมินผู้ป่วย และปัจจัยที่มีผลต่อการประเมิน เพื่อให้บุคลากรพยาบาลใช้เป็นแนวทางในการประเมินผู้ป่วย The Glasgow Coma Scale The Glasgow Coma Scale (GCS) is the gold standard for assessing the level of consciousness in patients with traumatic brain injury for over 40 years, and it has been improved over time. Access to current information of the scale allow users to use the scale efficiently. This article explains the standard approach, how to use the GCS in clinical practice, and factor affecting the accuracy of assessment, so nurses can use to guide the patient assessment.